Mechanisms of Organizing Pre-School Educational Organizations on the Basis of Public-Private Partnership - Khodzhiyev Sanjar Bakhtiyarovich (Peerian Journals Publishing, 2022)
Currently, special attention is paid to preparing children for high-quality school education in preschool educational organizations under the jurisdiction of the Ministry of Preschool Education of the Republic of Uzbekistan. This article aims to further develop the nongovernmental sector of preschool education services, ensure wider inclusion of children in the preschool education system, and create favorable conditions for public-private partnerships in the field of preschool education, as well as mechanisms for quality preparation of children for school education. 'shown
Keywords: Non-governmental preschool; education organization; child; program